Clinicopathologic, genomic and protein expression characterization of 356 ROS1 fusion driven solid tumors cases. Issue 7 (23rd December 2020) - Huang, Richard S. P.; Haberberger, James; Sokol, Ethan; Schrock, Alexa B.; Danziger, Natalie; Madison, Russell; Trabucco, Sally; Jin, Dexter; Pavlick, Dean; Ramanan, Vivek; Hole, Kanchan; McGregor, Kimberly; et al.
Abstract: Based on the approvals of crizotinib and entrectinib by the Food and Drug Administration for the treatment of ROS1 positive nonsmall cell lung cancer (NSCLC), we sought to examine the mutational profile of a variety of solid tumors (excluding sarcomas) with ROS1 fusions that underwent comprehensive genomic profiling. A review of our database was performed to extract all nonsarcoma patients with ROS1 fusions that were discovered by the hybrid capture‐based DNA only sequencing assays. We examined the coalterations representing potentially targetable biomarkers, resistance alterations and other alterations in these cases. In addition, we examined the histologic characteristics and protein expression with immunohistochemistry (IHC). From a series of clinically advanced nonsarcoma solid tumors, 356 unique cases with ROS1 fusions included 275 (77.2%) NSCLC and 81 (22.8%) non‐NSCLC. Ten novel ROS1 fusions were discovered. Importantly, the NSCLC ROS1 fusion pos tumors had a higher PD‐L1 IHC expression positivity when compared to the NSCLC ROS1 fusion neg population ( P = .012, Chi‐squared). The frequency of known and likely anti‐ ROS1 targeted therapy resistance genomic alterations in NSCLC was 7.3% (20/275) and in non‐NSCLC was 4.9% (4/81). Overall, the coalteration profile of ROS1 fusion pos NSCLC and non‐NSCLC was similar with only three genes altered significantly more frequently in non‐NSCLC vs NSCLC: TERT, PTEN, APC . In our study, we characterized a large cohort of ROS1 fusion pos NSCLC and non‐NSCLC solid tumors and discovered 10 novel ROS1 fusions. Abstract : What's new? When the ROS1 gene is rearranged, it can create fusion proteins that lead to various cancers. Anti‐ROS1 kinase inhibitors have been especially effective in non‐small cell lung cancer (NSCLC). In the present study, the authors found that the mutational profiles of ROS1 fusion‐positive, "non‐NSCLC" tumors were similar to those of NSCLC tumors. This suggests that ROS1‐targeted therapies might also hold promise for non‐NSCLC. In addition, PD‐L1 expression was high in ROS1 fusion‐positive NSCLC tumors, suggesting that checkpoint inhibitors might also provide a useful therapeutic strategy for those cancers.